Success Factors of SMEs: Empirical Study Guided by Dynamic Capabilities and Resources-Based View - Margarida Rodrigues (MDPI AG, 2021)
This study aims to identify and analyse the success factors of small and medium-sized enterprises (SMEs) following the lines of dynamic capabilities and resources-based views. To achieve this objective, the multiple case study method was followed, where 10 SMEs/cases in Portugal were selected. From a content analysis of the interviews conducted to the owner-managers of these SMEs, the most important success factors identified were: (1) strategic planning, (2) manager/management capacity, (3) entrepreneurship and innovation, (4) human resources, (5) networks/partnerships, and (6) financing. These factors are considered as drivers of sustained growth and creation of competitive advantage for SMEs in their regions. The results also show that SMEs are oriented towards success, although some evolution is still needed in the way they are managed, where the transition from a “domestic/entrepreneurial” management to a “professional” management and a greater focus on the rarity of their resources and on the dynamic capabilities of their human capital stand out. Conclusions, implications and a future research agenda are also outlined.